2017
DOI: 10.1088/1361-6528/aa9012
|View full text |Cite
|
Sign up to set email alerts
|

Facing the interaction of adsorbed silicon nano-ribbons on silver

Abstract: The atomic structure is one key property for any material. Despite great efforts during the last few years unveiling the internal structure of silicon nano-ribbons, analysis of the interfacial structure and bonding was neglected. We report on a comprehensive photoelectron spectroscopy and photoelectron diffraction study that reveals the weak interaction of silicon nano-ribbons with the underlying silver substrate identifying the specific locations of the individual silicon, as well as silver atoms. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
14
2
Order By: Relevance
“…In Figure 5a and that the Si-NaCl interaction is weak. This contrasts clearly with previous XPS studies of silicon on silver surfaces that showed two distinct components resulting from the two Si-Si and Si-Ag environments [9,10,52] . Figure 6 shows the modulus and the imaginary part of the Fourier transform of k 3 X(k) for bulk silicon and for the silicon layer grown on NaCl/Ag(110) surface.…”
Section: Stm Studies Of the Process Of Nacl Dissolution Show The Selecontrasting
confidence: 99%
See 3 more Smart Citations
“…In Figure 5a and that the Si-NaCl interaction is weak. This contrasts clearly with previous XPS studies of silicon on silver surfaces that showed two distinct components resulting from the two Si-Si and Si-Ag environments [9,10,52] . Figure 6 shows the modulus and the imaginary part of the Fourier transform of k 3 X(k) for bulk silicon and for the silicon layer grown on NaCl/Ag(110) surface.…”
Section: Stm Studies Of the Process Of Nacl Dissolution Show The Selecontrasting
confidence: 99%
“…Given that Si atoms are adsorbed on top of the NaCl film and that the Si-NaCl interaction is weak. This contrasts clearly with previous XPS studies of silicon on silver surfaces that showed two distinct components resulting from the two Si-Si and Si-Ag environments [9,10,52] . EXAFS measurements recorded at the Si K-edge provide complementary information on the local structure of the 2D silicon layer grown on NaCl/Ag(110) surface.…”
Section: Stm Studies Of the Process Of Nacl Dissolution Show The Selective Extraction Individualcontrasting
confidence: 99%
See 2 more Smart Citations
“…1(d)) was proposed for the nanoribbon structures 24 that satisfies DFT total energy calculations and high-resolution STM, core-level photoemission, and grazing-incidence xray diffraction experiments. 24,25 Further confirmation of a pentamer chain structure has recently been provided by photoelectron spectroscopy (XPS) and angle-resolved photoelectron diffraction (XPD) experiments, 26 as well as non-contact atomic force microscopy (nc-AFM) and tip-enhanced Raman spectroscopy (TERS). 27 Similar to Si/Ag(111), the Si/Ag(110) system thus consists of silicon adlayers strongly bonded to the Ag surface; nonethe-less there is little evidence to suggest that these structures retain any of the electronic features of a silicene-like layer, even when peeled off the substrate.…”
Section: Introductionmentioning
confidence: 99%